Formation of militia personnel in the 1960s. (Law and Safety, 2024)
The article examines the main aspects of recruitment, training and education of militia personnel in the 1960s. The overall shortage of personnel, especially qualified and experienced ones, continued to be significant in those years. In 1964–1967, almost half of the rank and file and junior militia officers changed hands. The ways in which professional training for the militia was organised, in particular through the Higher School of the Ministry of Internal Affairs of the USSR, Donetsk, Dnipro, Ivano-Frankivsk, Lviv and Odesa secondary specialised militia schools and the establishment of training and advisory centres at them, and the organisation of schools for improving operational skills, are shown. The formation of militia personnel during this period was largely carried out using the same methods as before, in particular, the leadership was recruited through the transfer of employees of party, Soviet and Komsomol bodies to the militia. In the 1960s, the militia staff was increased. The Ministry of Public Order and its local bodies paid considerable attention to political and educational work among militia officers, as had been the case throughout the Soviet period. To this end, in 1966, the activities of political departments were restored. Measures were taken to improve the financial situation and medical care of militia officers. The awarding of special ranks to those who served in the militia was regulated. The next special ranks of commanding officers could be assigned in a sequential order after the expiry of the established term and length of service in the previous rank in accordance with the new rank of the staff position held and in the presence of a positive attestation. However, during the period under study, there were numerous violations of discipline and the rule of law among militia officers, and their level did not decrease, and in some cases even increased. The state of countering crime was often ‘embellished’, crimes were concealed, and the rights of detainees were violated. The study and analysis of unsolved crimes showed that the lack of professional skills, especially of operatives, was one of the main reasons for the delayed solving of a number of serious crimes. Nevertheless, in general, it can be stated that the situation with militia personnel has improved somewhat at present.
Keywords: Ukraine; 1960s; Ministry of Public Order; militia; personnel; militia schools.